Grammatical errors in Essay writing: A study based on ESL students of English Department at South Eastern University of Sri Lanka - AMM Aaqil; RMF Rimaza; MR Inshafiqbal (Indonesian Journal of Social Research (IJSR), 2022)
Grammatical knowledge plays a crucial role in the process of writing. Most ESL learners are encountering several grammatical errors in their writing skills. For this reason, they are producing a different kind of grammatical errors, particularly in their Essay writing. This present study attempts to analyse the dominant grammatical errors and the causes of the errors which are committed by the ESL students of the English Department at the South Eastern University of Sri Lanka. The study was effectively conducted by collecting authentic data in relation to this topic. The data were collected from the sixteen selected ESL students by distributing a Google form, conducting an Interview, and finally placing an Essay writing test to evaluate their errors. After finishing the data collection, the grammatical errors were classified into eleven categories based on the questionnaire distribution and Essay writing test. Those identified grammatical errors were Capitalization, Spelling, Punctuation, Article, Preposition, Verb tense, Question, Subject-verb agreement, Word order, Word choice, and Plurality. The results of this data collection illustrate that the most dominant errors were Verb tense. Its percentage is 56.3%. The minority of errors were Plurality (6.3%). The second most dominant error was Word choice (43.8%). On the other hand, there were three types of grammatical errors Punctuation, Capitalization, and Subject-verb agreement, committed by the ESL students at the similar level (18.8%). 37.5% percentage of grammatical errors were in Spelling. The last first errors were Preposition, Word order, and Question in the equal level (12.5%). The current study investigated that the causes of errors were first language interference, lack of vocabulary knowledge, unawareness of tenses, poor speaking skills in the English language, and less writing practice. Meanwhile, the dominance of the first language was considered as the major cause of the students' errors in writing. In a nutshell, the ESL students of the English Department at the South Eastern University of Sri Lanka still have a serious problem in particular grammatical aspects. Therefore, at the end of this study, there were some beneficial suggestions suggested that the lecturers and the students must do some efforts to reduce the grammatical errors in writing.